The initial months of antiretroviral therapy and its influence on AGEs, HMGB1, and sRAGE levels in asymptomatic HIV-infected individuals - Tasca, Karen Ingrid [UNESP]; Caleffi, Juliana Trindade [UNESP]; Corrêa, Camila Renata [UNESP]; Gatto, Mariana [UNESP]; Camargo, Caio Cavassan De [UNESP]; Mendes, Monica Bannwart [UNESP]; Golim, Marjorie de Assis [UNESP]; Biasin, Mara; De Souza, Lenice Do Rosário [UNESP] (Hindawi, 2016)
The development of the typical comorbidities of aging which currently affects people living with HIV/AIDS (PLWHA) can be partially ascribed to the persistent immune activation and chronic inflammation characterizing these individuals. The aim of this study was to analyze the effect exerted by combined antiretroviral therapy (cART) administration on plasma levels of HMGB1 (high mobility group box protein-1), AGEs (advanced glycation end products), their soluble receptor sRAGE, cytokines, C-reactive protein (CRP), and some metabolic markers in asymptomatic PLWHA. Analyses were performed longitudinally in 30 PLWHA, before and about 6-12 months after cART initiation. We observed that lower levels of AGEs in post-cART group were accompanied by an increase of CRP and triglyceride levels already in the early months of therapy. Because of the current ever-earlier recommendations to start cART and its prolonged use, these and other markers should be investigated in order to monitor and postpone the appearance of non-AIDS comorbidities in PLWHA.